2016
DOI: 10.1371/journal.pone.0149138
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability Using Automatic Tracing with Canon OCT- HS100 and Zeiss Cirrus HD-OCT 5000

Abstract: BackgroundOptical coherence tomography (OCT), can be used in clinical practice to provide high resolution cross-sectional images of the retina, optic disc and macula structure. These measurements can be useful for early detection, diagnosis, monitoring and treatment guidance for retinal diseases. Therefore, repeatability of measurements in OCT is of great importance.MethodsMacula and optic disc parameters from the right eye of 30 healthy subjects were obtained twice with the Canon OCT-HS100 and Zeiss Cirrus HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…The A-scan rate in this device is 70,000 scans per second, while the scanning width is between 2 and 10 mm and the wavelength used is 855 nm. The axial resolution claimed is 3 μm with a scanning depth of 2 mm [ 12 ]. The OCT angiogram area selected for this study was 3 x 3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The A-scan rate in this device is 70,000 scans per second, while the scanning width is between 2 and 10 mm and the wavelength used is 855 nm. The axial resolution claimed is 3 μm with a scanning depth of 2 mm [ 12 ]. The OCT angiogram area selected for this study was 3 x 3 mm.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we used Zeiss Cirrus HD-OCT 5000. Brautaset et al [ 21 ] reported that the repeatability of this device is high in both macula and optic disc measurements because of its automatic tracking function. According to us, one of the major strengths of the present study was the demonstration of higher binocular RNFL thickness asymmetry in diabetic eyes compared to healthy eyes, which might indicate early inner retinal neurodegenerative process in DM without retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of modern commercial devices include additional hardware for correcting movement, such as retinal trackers [35], although the measurements generated by these instruments are not interchangeable [36]. A few examples are: Spectralis OCT (Heidelberg Engineering, Heidelberg, Germany), which uses auxiliary Scanning Laser Ophthalmoscopy (SLO) images; RTVue (Optovue Inc., Fremont, CA, USA), which uses a full-field fundus image; or tracking OCT from Physical Sciences Inc. (PSI, Andover, MA, USA), which uses a separate tracking beam for observing motion related reflectance changes of the retina [37].…”
Section: Prospective Approachesmentioning
confidence: 99%